2020
DOI: 10.1016/j.btre.2020.e00538
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin accumulation in the green microalga Haematococcus pluvialis: Effect of initial phosphate concentration and stepwise/continuous light stress

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…On the world market, there is an increase in interest in carotenoids from natural sources, including microalgae [11]. Microalgae such as Dunaliella salina, Haematococcus lacustris (=Haematococcus pluvialis), and some Chlorella are rich sources of carotenoids [37,38,48,66]. In microalgae capable of both autotrophic and heterotrophic growth (for example, Haematococcus lacustris and Chromochloris zofingiensis, formerly known as Chlorella zofingiensis), heterotrophic conditions can significantly increase the productivity of biomass, but they cannot provide large amounts of pigments, including commercially valuable ones [120].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
See 3 more Smart Citations
“…On the world market, there is an increase in interest in carotenoids from natural sources, including microalgae [11]. Microalgae such as Dunaliella salina, Haematococcus lacustris (=Haematococcus pluvialis), and some Chlorella are rich sources of carotenoids [37,38,48,66]. In microalgae capable of both autotrophic and heterotrophic growth (for example, Haematococcus lacustris and Chromochloris zofingiensis, formerly known as Chlorella zofingiensis), heterotrophic conditions can significantly increase the productivity of biomass, but they cannot provide large amounts of pigments, including commercially valuable ones [120].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
“…In microalgae capable of both autotrophic and heterotrophic growth (for example, Haematococcus lacustris and Chromochloris zofingiensis, formerly known as Chlorella zofingiensis), heterotrophic conditions can significantly increase the productivity of biomass, but they cannot provide large amounts of pigments, including commercially valuable ones [120]. Exposure to high-intensity lighting increases carotenoid production in Haematococcus lacustris [37,121], Dunaliella salina [48,79], Chromochloris zofingiensis [122], Tetradesmus obliquus [123], Nostoc calcicola [124], etc. (Table 5).…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…H. pluvialis contains about 5% of astaxanthin (dry weight) and its production is regulated by different stress conditions and its related with H, pluvialis cell cycle [23] . Several studies have shown that high light intensity, high salinity of the medium, pH, temperature, and lack of nutrients, stimulate H. pluvialis to produce astaxanthin [24] , [25] , [26] , reaching even about 7% in soils poor in phosphorus [27] or thank to a photoautotrophic induction [28] . Astaxanthin production usually occurs in two different stages [29] .…”
Section: Introductionmentioning
confidence: 99%